The Impact of Online Games on Adolescent Health in Umbul Rowo Hamlet - Miftahul Munir; Mashudi Ma’ruf; Emawati Dwi Astuti; Siti Roudhotul Jannah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to analyze the influence of online gaming on the mental health of adolescents in Dusun Umbul Rowo. The background of this study is based on the increasing use of online games among teenagers, which impacts various aspects of life, particularly mental health. The method used is a quantitative approach with a survey technique. The sample in this study consists of 32 adolescents aged 13–18 years, selected purposively. Data was collected through closed questionnaires and analyzed using simple linear regression tests. The results of the study indicate a significant influence between the intensity of online gaming and the mental health of adolescents, with a significance value of 0.002 (< 0.05). The longer the gaming duration, the greater the tendency for respondents to experience sleep disturbances, anxiety, and reduced social interaction. However, some respondents also reported emotional and cognitive benefits from gaming, such as decreased stress and improved focus. This research emphasizes the importance of monitoring online gaming usage and the need for education on mental health to prevent long-term negative impacts.